Effect of alkali treatment and fibre composition on the performance of pineapple leaf fibre-polyvinyl alcohol composites - Hanis Nurafiqah Zubairi; Noordini M. Salleh; Nor Mas Mira Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper studied the properties of composites based on polyvinyl alcohol reinforced with pineapple leaf fibres (PALF/PVA). The surface of pineapple leaf fibres (PALF) has been previously treated with 6% sodium hydroxide solution. The influence of fibre loading and fibre surface treatment were examined. Analysis by Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) displayed physico-chemical changes on treated PALF/PVA composites compared to untreated PALF/PVA composites. The results from thermogravimetric analysis (TGA) showed that the introduction of untreated PALF into the composites enhanced the thermal stability of the composites. Progressive improvement of thermal stability was discovered by associating treated PALF with the composites. The treated PALF composites produced also improved mechanical properties with increasing fibre content. Differential scanning calorimetric (DSC) analyses showed no significant changes in melting temperatures upon incorporating untreated PALF into the PALF/PVA composites. The best improvement in tensile strength value was obtained for treated PALF composite having 3 wt% of fibre loading, with enhancements of about 11% and 54%, compared to untreated PALF composites and plain PVA matrix, respectively.